KUAT TEKAN DAN MODULUS ELASTISITAS BETON DENGAN PENAMBAHAN STYROFOAM (STYROCON) - Dharma Giri, Ida Bagus; Sudarsana, I Ketut; Tutarani, Ni Made (Jurnal Ilmiah Teknik Sipil, 2012)
This experiment is aimed to know the value of compressive strength and elastic modulus of concrete by adding granular styrofoam and also relationship between compressive strength and elastic modulus of concrete by percentage increased granular styrofoam. Granular styrofoam is used by consideration it can reduce the weight of concrete but still has enough strength to arrest loads. The comparison of mixture is 1 : 2 : 3 (cement : sand : crush stone) by comparison of weight with water cement ratio is 0,50 and maximum size of aggregates are 25 mm. Variation of percentage increased granular styrofoam are 0%, 10%, 20%, 30%, 40% to volume of mixture. The range of diameter granular styrofoam are 3-10 mm, with volume of weight 22,89 kg/m3. The specimen for compression and elastic modulus test in cylindrical form by size 150 mm of diameter and 300 mm of height with amount 7 specimens for each percentage increased granular styrofoam where 5 specimens are read the change of length to get modulus of elasticity. The tests are done when specimens age 28 days. Experiment results show that compressive strength and elastic modulus decrease with increased percentage granular styrofoam which add to concrete mixture. The value of compressive strength by adding granular styrofoam 0%, 10%, 20%, 30%, 40% are 32,395 MPa, 24,144 MPa, 17,994 MPa, 13,411 MPa, 9,995 MPa. Decreased of elastic modulus by adding granular styrofoam 10%, 20%, 30%, 40% based on ASTM C 469 are 0,278%, 5,797%, 16,555%, and 32,553%, and based on slope of the stress-strain curve are 0,587%, 6,256%, 17,006%, and 32,838%.
Keywords: kuat tekan, modulus elastisitas, styrofoam